2021
DOI: 10.1080/09286586.2021.1974494
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment, Eye Disease, and 3-Year Cognitive Decline: The Canadian Longitudinal Study on Aging

Abstract: Purpose: To examine the longitudinal association between vision-related variables and the 3-year change in cognitive test scores in a community-dwelling sample of adults and to explore whether sex, education, or hearing loss act as effect modifiers. Methods: Data came from two waves of a 3-year population-based prospective cohort study (Canadian Longitudinal Study on Aging), which consisted of 30,097 randomly selected people aged 45-85 years from 7 Canadian provinces. Visual impairment (VI) was defined as bino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, a prospective cohort research revealed that there was no link between depression and glaucoma, which was inconsistent with findings forementioned (Vidal et al, 2021). Also, a 3-year longitudinal study consisting of 30,097 individuals aged 45-85 years did not find an association between glaucoma and depression (Grant et al, 2021). These contentious findings may be influenced by indissoluble or unidentified risk factors in observational studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a prospective cohort research revealed that there was no link between depression and glaucoma, which was inconsistent with findings forementioned (Vidal et al, 2021). Also, a 3-year longitudinal study consisting of 30,097 individuals aged 45-85 years did not find an association between glaucoma and depression (Grant et al, 2021). These contentious findings may be influenced by indissoluble or unidentified risk factors in observational studies.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, retinal nerve fiber layer thinning and neural cell loss in the ganglion cell layer were observed in the chronic unpredictable mild stress mouse model, indicating that psychological stress could induce glaucoma-like changes (Zhang et al, 2022). While some other epidemiological findings suggested that there was no association between depression and glaucoma (Rezapour et al, 2018;Vidal et al, 2021;Grant et al, 2021), which made this relationship contentious. Establishing a definitive etiological link may be challenging due to the presence of confounding factors and the potential for reverse causation in traditional epidemiological findings.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research suggests that AMD is associated with functional and structural visual cortex abnormalities, as well as cognitive decline. Recent imaging studies support this by showing an association between macular degeneration and cognitive decline [14,15]. Szlyk et al also reported that patients with AMD developed abnormal cerebral network changes that increased prefrontal and parietal activation [16].…”
Section: Introductionmentioning
confidence: 97%
“…Among people with glaucoma, the prevalence of MCI and dementia ranged from 12.3% to 90.2% and from 2.5% to 3.3%, respectively [10]. In a 3-year population-based prospective cohort study, glaucoma was associated with greater declines in Mental Alternation Test scores and worsening processing speed [11].…”
Section: Introductionmentioning
confidence: 99%